2019
DOI: 10.1002/jbmr.3700
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Osteoporosis Screening Using Biomechanical Computed Tomography for Patients With a Previous Abdominal CT

Abstract: Osteoporosis screening rates by DXA are low (9.5% women, 1.7% men) in the US Medicare population aged 65 years and older. Addressing this care gap, we estimated the benefits of a validated osteoporosis diagnostic test suitable for patients age 65 years and older with an abdominal computed tomography (CT) scan taken for any indication but without a recent DXA. Our analysis assessed a hypothetical cohort of 1000 such patients in a given year, and followed them for 5 years. Separately for each sex, we used Markov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…With a clinical focus in mind, the body of evidence reviewed here supports the following: When utilizing hip-containing CT exams of the abdomen or pelvis, BCT performed at the hip is particularly effective for identifying patients at high risk of hip fracture. With about seven million CT exams of the abdomen or pelvis being performed each year in the US Medicare population [27], opportunistic BCT at the hip should help improve osteoporosis care for this population and may do so in a cost-effective manner compared to usual care DXA testing [94]. For non-CT patients, DXA testing remains appropriate as per current guidelines, unless there are specific reasons to order a BCT with a dedicated CT-patients presenting without BMD-defined osteoporosis but with an otherwise unexplained fracture or patients with appreciable vertebral degeneration [55] or aortic calcification [47].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a clinical focus in mind, the body of evidence reviewed here supports the following: When utilizing hip-containing CT exams of the abdomen or pelvis, BCT performed at the hip is particularly effective for identifying patients at high risk of hip fracture. With about seven million CT exams of the abdomen or pelvis being performed each year in the US Medicare population [27], opportunistic BCT at the hip should help improve osteoporosis care for this population and may do so in a cost-effective manner compared to usual care DXA testing [94]. For non-CT patients, DXA testing remains appropriate as per current guidelines, unless there are specific reasons to order a BCT with a dedicated CT-patients presenting without BMD-defined osteoporosis but with an otherwise unexplained fracture or patients with appreciable vertebral degeneration [55] or aortic calcification [47].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To quantify the potential clinical impact of opportunistic BCT for the CT-patient, a theoretical cost-effectiveness study [94] simulated a hypothetical cohort of 1000 Medicare patients who had undergone an abdominal CT for any medical indication but were without a recent DXA. All those "DXA-lacking" CT patients were offered BCT, 90% were successfully tested,…”
Section: Bct Measurements Are Precise and Clinically Reproduciblementioning
confidence: 99%
“…A CT-based prediction tool based on linear regression was developed, using as input three bone imaging biomarkers along with age and sex data; contribution of FRAXwb to the CT-based prediction tool was also assessed. The authors concluded that when FRAXwb input is not available, the initial evaluation of fracture risk can be carried out automatically based on a single abdomen or chest CT. Biomechanical computed tomography (BCT) has been proposed to identify high fracture risk patients based on both femoral strength and hip BMD T-scores [69]. The clinical outcomes were obtained using a four states Markov model along a year, which includes: presence and absence of hip fractures, osteoporosis treatment, and bone's death (absorbing state).…”
Section: Quantitative Computed Tomographymentioning
confidence: 99%
“…In the US Medicare population, for example, osteoporosis screening rates by DXA (dual energy xray absorptiometry) are as low as 9.5 percent for women and 1.7 percent for men aged 65 and over. As a result, osteoporosis screening with biomechanical computed tomography may be a cost-effective alternative to current standard therapy for individuals who have had an abdomen CT and have not had a recent DXA (Pisu et al, 2019). The imaging and quantification of bone and bone mineral density are crucial in the diagnosis of osteoporosis.…”
Section: Diagnosis and Screening Strategiesmentioning
confidence: 99%